Abnormal frontostriatal activity in recently abstinent cocaine users during implicit moral processing - Caldwell, Brendan M.; Harenski, Carla L.; Harenski, Keith A.; Fede, Samantha J.; Steele, Vaughn R.; Koenigs, Michael R.; Kiehl, Kent A. (Frontiers in Human Neuroscience, 2015)
Investigations into the neurobiology of moral cognition are often done by examining clinical populations characterized by diminished moral emotions and a proclivity toward immoral behavior. Psychopathy is the most common disorder studied for this purpose. Although cocaine abuse is highly co-morbid with psychopathy and cocaine-dependent individuals exhibit many of the same abnormalities in socio-affective processing as psychopaths, this population has received relatively little attention in moral psychology. To address this issue, the authors used functional magnetic resonance imaging (fMRI) to record hemodynamic activity in 306 incarcerated male adults, stratified into regular cocaine users (n = 87) and a matched sample of non-cocaine users (n = 87), while viewing pictures that did or did not depict immoral actions and determining whether each depicted scenario occurred indoors or outdoors. Consistent with expectations, cocaine users showed abnormal neural activity in several frontostriatial regions during implicit moral picture processing compared to their non-cocaine using peers. This included reduced moral/non-moral picture discrimination in the vACC, vmPFC, lOFC, and left vSTR. Additionally, psychopathy was negatively correlated with activity in an overlapping region of the ACC and right lateralized vSTR. These results suggest that regular cocaine abuse may lead to affective deficits which can impact relatively high-level processes like moral cognition. Moreover, they add to a growing body of research suggesting an important role for the mesocorticolimbic dopamine pathway in socio-affective processing.